Indigenous and colonial Health Policy in Tahuantinsuyo - Monge M., Carlos (2014)
The existence of populations acclimated to life in the great heights of America inhabited since prehistoric times, between 2000 to 6000 meters above sea level, a need to study the Andean Biology: man, plants and animals. The characteristics of the man of the Andes that are specific morphological and physiological aspects, have been laid down for us in the best of our ability, in the Medical School of Lima.